Potential of the DSP-based Method for Fast Precise Event Timing - Artyukh, Yu.; Bespal’ko, V.; Boole, E. (Elektronika ir Elektrotechnika, 2009)
General principles of high-precision event timing based on DSP approach are discussed with emphasis made on the particular fast method for such event timing. The latest specific implementation of this method and its main features (basic error components, achievable final precision and operation speed) are considered in more details. By this example it is shown that the method can provide picosecond precision at measurement rate up to tens of MHz. Ill. 4, bibl. 6 (in English; summaries in English, Russian and Lithuanian)..